Is Distant Extension Always Upset? Neural Evidence of Empathy and Brand Association Affect Distant Extension Evaluation - Song, Zhijie; Liu, Chang; Shi, Rui; Jing, Kunpeng (Frontiers in Psychology, 2022)
Distant brand extension as an essential strategy of obtaining benefits was highly focused on by the normal marketing practice and academic research. In the current study, we aim to recognize that how individuals with different levels of empathy respond to distant extensions under corporate social responsibility (CSR) and corporate competence (CC) associations to explore the corresponding neural mechanisms using event-related potentials (ERPs). We divided subjects into two groups involving a high empathy (HE) group and low empathy (LE) group according to an empathy measure questionnaire. The subjects first faced a brand name following corporate social responsibility (CSR) or corporate competence (CC) association descriptions, and then, they were asked to evaluate the brand’s new product by a five-point scale. Current results revealed that the participants of the HE group were more apt to accept the distant extension products than those of the LE group. And in the HE group, products from a brand with CSR associations were more acceptable than CC associations. Moreover, a larger N2 amplitude was elicited in the LE group than in the HE group. For the LE group, an augment N2 was found under CSR than CC associations, reflecting that LE consumers might perceive conflict when evaluating distant extensions and allocate more cognitive resources to deal with CSR information. At the later stage, the HE group showed a greater P3 than the LE group. For the HE group, an increased P3 was elicited under CSR than CC associations, suggesting that empathic individuals might show motivational salience and helping willingness toward distant extension products, especially under the CSR scenario. These results provide potential electrophysiological evidence for the positive impact of brand associations on the evaluation of distant brand extension in the case of subdividing different empathic individuals.